The life and opinions of the Tomcat Murr : together with a fragmentary biography of Kapellmeister Johannes Kreisler on random sheets of waste paper /: together with a fragmentary biography of Kapellmeister Johannes Kreisler on random sheets of waste paper. (2006) - Hoffmann, E. T. A (Ernst Theodor Amadeus), 1776-1822
No abstract available